Identification of control parameters of the permanent magnetic synchronous generator using least square method. (July 2022) - Yin, Hongxu; Wei, Yanfei; Zhang, Yingjie; Jing, Panpan; Cai, Deyu; Liu, Xumin
Abstract: This paper presents a new methodology for the identification of the control parameters of converters of Direct-drive Permanent Magnetic Synchronous Generator (DPMSG) using least square method. Firstly, the novel methodology for the control parameter identification was thoroughly introduced; after that, a complete model of DPMSG was built in DIgSILENT PowerFactory platform for generating testing signals; finally, the algorithm was tested through signals obtained using dynamic simulations of the complete model of DPMSG. The accurate estimation was obtained by this methodology, i.e. the maximum error of the identification results was less than 3.1%. This method was able to accurately identified the converter control parameters of DPMSG without setting initial values for the identification program.